Transformações alotrópicas de carbono induzidas por irradiação com feixe de elétrons - Silva, Vinícius Teodoro da (2021)
In the last years, the carbon has attracted scientific and technological interest due to its different allotropic forms, as graphite, graphene, fullerene, and carbon nanotubes, which present unique and promising properties. These properties can be applied in several areas, as photonics, solar cells and energy storage, superconductivity, sensors and biosensors, photocatalysis, and others. Besides that, a recent study has demonstrated that carbon-based nanomaterials are promising antiviral agents against the SARS-CoV-2 virus, thus contributing for the control of COVID-19 pandemic. In this way, the preparation of a material with different carbon structures is promising for the development of a functional material, which can be applied in several areas. Herewith, this thesis has as main objective the allotropic transformation of carbon by the electron beam irradiation and the understanding of this interaction. For this, graphite pellets were prepared and irradiated by the electron beam irradiation system in different times, which were 2, 4, 8, 16, and 32 minutes. The obtained materials were characterized by X ray diffraction, Micro-Raman scattering spectroscopy, X ray photoelectron spectroscopy, Scanning electron microscopy, Transmission electron microscopy with Energy-dispersive X ray spectroscopy and Selected area electron diffraction, and Focused ion beam scanning electron microscopy. According to the obtained results, the electron beam irradiation system promoted the sputtering of the Fe that composes the high acceleration anode, which acted as catalyst for the fullerene formation (C60). Subsequent processes induced by the interaction with the electron beam promoted the onion-like fullerene, which coalesced with each other and formed multiwalled carbon nanotubes with embedded magnetite nanoparticles (Fe3O4). Furthermore, these carbon nanotubes, induced by the electron beam, unroll to form the rod-like particles, which grew vertically oriented on the pellet surfaces. Therefore, the electron beam irradiation allowed the formation of fullerene and carbon nanotubes with embedded magnetite nanoparticles, being a promising method for the preparation carbon-based multifunctional materials.